Easing Parental Worries: A Systematic Review and Network Meta-analysis on Preoperative Education Methods for Reducing Anxiety in Parents of Children Undergoing Surgery - Saundarya Priyadarshini; Sandeep Agarwala; Harsh Priya; Vishesh Jain; Prabudh Goel; Anjan Dhua; Devendra Kumar Yadav (Journal of Indian Association of Pediatric Surgeons)
Parental anxiety during the time leading up to a child’s surgery is a major concern. One approach that’s gained attention for helping ease this stress is preoperative education, but there’s still no clear agreement on which type of educational method works best. This review looked into a range of educational strategies to find out which ones are most effective at lowering anxiety in parents. Between January and March 2024, researchers conducted an extensive search across databases like PubMed, EMBASE, Web of Science, and Google Scholar. They focused on studies that evaluated preoperative education for parents, specifically targeting those that measured parental anxiety using validated tools. From this search, 23 studies were included in the final review, and 19 of them, involving nearly 2,000 participants, were analyzed in a network meta-analysis. The interventions examined varied and included things like videos, web-based platforms, printed booklets, multimedia content, and educational games. When all the data were compared, web-based education stood out as the most effective, with a significant reduction in anxiety levels (SMD = −1.40). Video-based approaches also helped, though to a lesser extent (SMD = −0.42). On the other hand, booklets and game-based education didn’t seem to have as strong an impact. In short, web-based educational tools appear to be the best option for helping parents manage the stress of their child’s upcoming surgery. These findings could help hospitals and surgical teams choose the most effective ways to prepare and support families during this challenging time.